2003
DOI: 10.1016/s0304-3835(02)00108-8
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic implantation of a colon cancer xenograft induces high expression of cyclooxygenase-2

Abstract: The aim of the present study is to investigate the relation of cyclooxygenase (COX)-2 with liver metastasis. Pieces of human colon cancer xenograft were implanted orthotopically (CI), as well as intraperitoneally, and subcutaneously. Liver metastasis developed most frequently, and the COX-2 expression of both mRNA and protein of the tumors was the most dominant in the CI group. In contrast, the expression of COX-1 or vascular endothelial cell growth factor mRNAs had no significant differences among the groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In a previous study, we confirmed that TK-4 expresses VEGF-A, cyclooxygenase (COX)-1, COX-2 (24), and the active form of matrix metalloproteinase-2 (42). COX-2 expression was significantly up-regulated in the orthotopically implanted tumors and was positively correlated with the number of liver metastases (24).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In a previous study, we confirmed that TK-4 expresses VEGF-A, cyclooxygenase (COX)-1, COX-2 (24), and the active form of matrix metalloproteinase-2 (42). COX-2 expression was significantly up-regulated in the orthotopically implanted tumors and was positively correlated with the number of liver metastases (24).…”
Section: Discussionmentioning
confidence: 52%
“…In a previous study, we confirmed that TK-4 expresses VEGF-A, cyclooxygenase (COX)-1, COX-2 (24), and the active form of matrix metalloproteinase-2 (42). COX-2 expression was significantly up-regulated in the orthotopically implanted tumors and was positively correlated with the number of liver metastases (24). Kaplan and colleagues (23) have shown that VEGF and placental growth factor derived from tumor cells up-regulate fibronectin in resident fibroblasts, which results in the activation of VEGFR1-positive hematopoietic bone marrow progenitor cells in premetastatic organs, providing a permissive niche for incoming tumor cells.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…To assess the local invasion and metastatic potential of sprouty-2 up-regulated HCT-116 cells, we performed cecal orthotopic tumor implantations (Shoji et al, 2003). Mice were anesthetized with ketamine (70 mg/kg body wt) and Xylazine (7 mg/kg body wt).…”
Section: Methodsmentioning
confidence: 99%
“…It has been extensively documented that overexpression of COX-2 is implicated in various forms of human cancers such as cancer of the lung [26], breast [27], colorectal [28], prostate [29], head and neck [30] and others [31,32]. In particular, increased COX-2 expression has been brought in connection with tumour metastasis in colon cancer [33] where aberrant COX-2 expression was shown to correlate with carcinogenesis in more than 80% of colorectal cancers [34]. In animal models COX-2 expression was found to be sufficient to induce tumourigenesis [35].…”
Section: The Cox Pathwaymentioning
confidence: 99%